Chlamydia trachomatis: impact on human reproduction - Paavonen, Jorma; Eggert-Kruse, Waltraud (Human reproduction update, 1999)
Chlamydia trachomatis infections are the most prevalent bacterial sexually transmitted infections (STI) recognized throughout the world. Worldwide, the magnitude of morbidity associated with sexually transmitted chlamydial infections is enormous. C.trachomatis is a common cause of urethritis and cervicitis, and sequelae include pelvic inflammatory disease (PID), ectopic pregnancy, tubal factor infertility, epididymitis, proctitis and reactive arthritis. The sharp worldwide increase in the incidence of PID during the past two decades has led to the secondary epidemics of tubal factor infertility and ectopic pregnancy...